Indications and outcomes of rivaroxaban use in cats - Ella Yarsley; Claire R. Sharp; Claire R. Sharp; Corrin J. Boyd; Joonbum Seo; Joonbum Seo; Erin Mooney (Frontiers in Veterinary Science)
IntroductionThe use of rivaroxaban, an oral direct factor Xa inhibitor, has only been described in a small number of publications in cats. The study objective was to describe the use of rivaroxaban in a large population of hospitalised cats.MethodsCases were retrospectively identified from June 2017 to July 2024 at seven veterinary specialty hospitals. Any cat prescribed rivaroxaban was eligible for inclusion. Data extracted from the medical records included signalment (age, sex, breed), body weight, reason for commencing rivaroxaban, dose and duration of rivaroxaban, concurrent anticoagulant and antiplatelet therapies, potential rivaroxaban adverse effects, and outcome. Non-parametric descriptive statistics are reported.ResultsIn total, 66 cats were included. Median rivaroxaban dose was 2.5 mg (Min-Max 1.25–10, Q1-Q3 2.5–5.0), equal to 0.73 mg/kg/day (Min-Max 0.28–1.87, Q1-Q3 0.53–1.0). A total of 36 cats (54.5%) were within the suggested dose range of 0.5–1 mg/kg/day of the Consensus on the Rational Use of Antithrombotics in Veterinary Critical Care (CURATIVE) guidelines, 14 (21.2%) were below, while 16 (24.2%) were above. Median duration of rivaroxaban was 26.5 days (Min-Max 0–442, Q1-Q3 2–60), although followup was variable. The indication for rivaroxaban administration was confirmed thrombosis (48, 72.7%), strong clinical suspicion of thrombosis (6, 9.1%), and prophylaxis (12, 18.2%). Most thrombi were arterial, including aortic thromboembolism affecting both pelvic limbs (25/54 cats with thrombosis, 46.3%), arterial thrombosis affecting a single limb (16, 29.6%), and cardiac chamber thrombus (7, 13%). Cardiac disease was the most common thrombosis risk factor (53/66, 80.3%). Other CURATIVE defined risk factors included immune-mediated haemolytic anaemia in four cats (6.1%) and sepsis in one cat. Other thromboprophylaxis administered included clopidogrel in 58 cats (87.9%), dalteparin in 8 cats (12.1%), and aspirin in 4 cats (6.1%). Potential adverse effects prompting rivaroxaban discontinuation included one case each of vomiting, a cerebrovascular accident, gastrointestinal bleeding, and haemorrhagic pleural effusion. Forty-five cats (68.2%) survived to hospital discharge, 14 (21.2%) were euthanised, two (3%) died, and five (7.6%) were taken home against medical advice.ConclusionRivaroxaban was well tolerated in a large population of cats, predominantly prescribed for arterial thrombosis associated with cardiac disease.